1994
DOI: 10.1128/jvi.68.11.7637-7643.1994
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of a human neurotropic virus promoter in glial cells: effect of YB-1 on expression of the JC virus late gene

Abstract: We have isolated a partial recombinant cDNA clone from a HeLa expression library which encodes a protein capable of binding to the central region of the human neurotropic JC virus (JCV) enhancer/promoter, termed the B region. Sequence analysis revealed a complete homology of the partial cDNA clone to the N-terminal region of a previously described DNA-binding protein, termed YB-1. Band shift analyses have indicated that the bacterially produced YB-1 interacts specifically with the double-stranded B oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“…In earlier studies, we demonstrated that YB-1, a DNA binding protein which recognizes the inverted CCAAT sequence, may exert its regulatory action upon communication with other cellular proteins, including NF-B subunits via the D-regulatory motif (39). Moreover, we demonstrated that YB-1 could bind to another viral regulatory motif, the LCE (26). As the 23-bp sequence, by disrupting the LCE motif, may affect its regulatory action on the JCV genome, we performed a series of structural and functional studies to analyze the functional importance of the 23-bp sequence for JCV gene transcription.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In earlier studies, we demonstrated that YB-1, a DNA binding protein which recognizes the inverted CCAAT sequence, may exert its regulatory action upon communication with other cellular proteins, including NF-B subunits via the D-regulatory motif (39). Moreover, we demonstrated that YB-1 could bind to another viral regulatory motif, the LCE (26). As the 23-bp sequence, by disrupting the LCE motif, may affect its regulatory action on the JCV genome, we performed a series of structural and functional studies to analyze the functional importance of the 23-bp sequence for JCV gene transcription.…”
Section: Discussionmentioning
confidence: 87%
“…Results from earlier studies led us to believe that the pentanucleotide repeat sequence, also referred to as the lytic control element (LCE), has the ability to modulate JCV early and late promoters (44,45) and contributes to viral DNA replication (10,30). In subsequent studies, two cellular single-stranded DNA binding proteins named Pur␣ and YB-1, which recognize purine-rich and C/T-rich sequences, respectively, of the LCE, were identified (12,26,44). Results from subsequent studies indicated that in JCV Mad-1 , binding of YB-1 to its DNA target within the LCE is increased by Pur␣.…”
mentioning
confidence: 99%
“…The function of the somatic Y-box proteins is unknown. They have been proposed to also influence the translation of mRNA (Evdokimova et al, 1995); however, other experiments suggest a role in transcriptional control Wolffe, 1990, 1992;Ting et al, 1994;Kashanchi et al, 1994;Kerr et al, 1994;MacDonald et al, 1995). Our definition of the Y-box proteins as capable of sequenceselective RNA recognition provides a potential explanation for their selective influence on the transcription process independent of specific association with DNA.…”
Section: Table II Rna Binding By Frgy2mentioning
confidence: 79%
“…Since Y-box binding proteins exhibit a high degree of primary sequence conservation, particularly in the central DNA binding domain, it has been suggested that they may have essential structural and functional roles in eukaryotic cells. In fact, a growing body of experimental evidence indicates that Y-box binding proteins are involved in a wide variety of biological functions, including regulation of gene expression at both the transcriptional (2,10,13,25,26,32,37,38) and translational (48) levels, DNA and RNA condensation, and DNA repair (21,52,53). In addition, recent reports indicate that the members of the Y-box family of proteins are responsive to many types of stress-related stimuli, including UV irradiation (8,28), drug treatment (3,32), DNA damage (24,28), and interleukin-2 treatment in T cells (45).…”
mentioning
confidence: 99%